Penerapan Structural Equation Modeling (SEM) dalam Bidang Pendidikan - Zuhairoh, Faihatuz (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFThis study discusses the application of SEM in the field of education on the relationship between quality of service (ξ1), satisfaction (η1), confidence (η2) and loyalty (η3) are also basic concepts SEM, structural equation modeling and make a path diagram. This study aimed to determine the relationship of service quality, satisfaction, trust and loyalty student at UNM Department of Mathematics and knowing intervening variable between service quality and loyalty. Using SEM analysis found that the quality of service significantly influence satisfaction and trust while the quality of service does not have a significant direct influence loyalty. Satisfaction was also no significant effect on loyalty. Structural equation modeling results are , , . From the analysis it can be concluded that loyalty can be built with good quality service with confidence as an intervening variable. So, with good service will lead to student confidence. Once there is trust there arise loyalty. Key words: SEM, service quality, satisfaction, trust, loyalty.